2020
DOI: 10.3389/fonc.2019.01504
|View full text |Cite
|
Sign up to set email alerts
|

Sub-acute Toxicity in Non-cancerous Tissue and Immune-Related Adverse Events of a Novel Combination Therapy for Cancer

Abstract: Brain, lung, and colon tissue experience deleterious immune-related adverse events when immune-oncological agents or radiation are administered. However, there is a paucity of information regarding whether the addition of radiation to immuno-oncological regimens exacerbates the tissue inflammatory response. We used a murine model to evaluate sub-acute tissue damage and the systemic immune response in C57Bl/6 mice when administered systemic anti-programmed cell death protein 1 (αPD-1) immunotherapy alone or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Tumors treated with TMZ and/or RT and all-combined treatment showed increased DNA damage (γH2A.X; p < 0.001; Figure 9C). We have previously observed this phenomenon of prolonged γH2A.X at 28 days after RT treatment in noncancerous brain, lung, and colon tissues (24). As the patterning is not observed in unirradiated (untreated) brains, we believe that it indicates radiotoxicity to the "healthy" cells, including radiosensitive oligodendrocytes, which have shown limited regenerative capacity out to 18-month postirradiations (29).…”
Section: Dca/rano Increases In Vivo Murine Gbm Survivalmentioning
confidence: 76%
See 3 more Smart Citations
“…Tumors treated with TMZ and/or RT and all-combined treatment showed increased DNA damage (γH2A.X; p < 0.001; Figure 9C). We have previously observed this phenomenon of prolonged γH2A.X at 28 days after RT treatment in noncancerous brain, lung, and colon tissues (24). As the patterning is not observed in unirradiated (untreated) brains, we believe that it indicates radiotoxicity to the "healthy" cells, including radiosensitive oligodendrocytes, which have shown limited regenerative capacity out to 18-month postirradiations (29).…”
Section: Dca/rano Increases In Vivo Murine Gbm Survivalmentioning
confidence: 76%
“…Drugs used in this study were DCA (sodium DCA #347795; Sigma-Aldrich, St. Louis, MO, USA), TMZ (#T2577; Sigma-Aldrich St. Louis, MO, USA), and Rano (Rano dihydrochloride #R6152; Sigma-Aldrich St. Louis, MO, USA) dissolved in complete media for in vitro studies and in sterile water for in vivo studies at stock concentrations of 40, 5, and 10 mg/ml, respectively. X-ray radiation was delivered using the Small Animal Radiation Research Platform (SARRP; Xstrahl Inc., Suwanee, GA, USA) at a dose rate of 2.97 Gy/min as described earlier ( 24 ). In all experiments, the drug treatment preceded irradiation by 1 h to enable the drugs to act on their respective cellular targets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the EORTC protocol, 60 Gy is delivered in 30 fractions of 2 Gy per day over 6 weeks. We previously reported that RT of non-cancerous tissue can alter cell proliferation, blood vasculature and immunity in the sub-acute period (28 days) after conventional fractionated RT [ 21 ]. The current study assessed the biological effect of higher RT doses with fewer fractions (10 Gy/2 f per week) could reduce tumor growth, induce greater anti-tumor immunoreactivity, and minimise delayed radionecrosis compared to a conventional fractionated regimen (10 Gy/5 f per week).…”
Section: Discussionmentioning
confidence: 99%